Human papillomavirus vaccine effectiveness by age at vaccination: A systematic review - Mallory K. Ellingson; Hassan Sheikha; Kate Nyhan; Carlos R. Oliveira; Linda M. Niccolai (Taylor & Francis Group, 2023)
Human papillomavirus (HPV) vaccines work by preventing infections prior to natural exposure. Thus, it is likely more effective at younger ages, and it is important to understand how effectiveness might be diminished when administered at older ages. We conducted a systematic review of HPV vaccine effectiveness studies published between 2007 and 2022 that included an analysis of effectiveness against vaccine-type HPV infections, anogenital warts, cervical abnormalities and cervical cancer by age at vaccine initiation or completion. Searching multiple databases, 21 studies were included and results were summarized descriptively. Seventeen studies found the highest vaccine effectiveness in the youngest age group. Vaccine effectiveness estimates for younger adolescents ages 9-14 years ranged from approximately 74% to 93% and from 12% to 90% for adolescents ages 15-18 years. These results demonstrate that the HPV vaccine is most effective against HPV-related disease outcomes when given at younger ages, emphasizing the importance of on-time vaccination.